Anmerkungen zu den Beziehungen der mittellateinischen und der ungarischen Textraditionen der Vita Margarite de Hungaria Ordinis Predicatorum - M. Nagy, Ilona (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The oldest Latin legend of Saint Margaret of Hungary (legenda vetus, LV, about 1275) survived in only one manuscript, a copy found in Bologna, dated to the beginning of 15th century (1409-10). The text of the legend in the manuscript is in many places debased and to some extent shortened. This paper deals with the question how the Medieval Hungarian legend of Saint Margaret (the only surviving copy from 1510), which contains almost the complete text of LV in vernacular translation, can help in correcting the manuscript and reconstructing the original text of the oldest Latin legend. Medieval German translations of LV are also referred to. Some special problems of the edition (1937) are mentioned in this connection as well.